WORKING WITH MATHEMATICALLY GIFTED STUDENTS AGED 16-17 (Balkan Journal of Applied Mathematics and Informatics, 2022)
The goals and activities of almost all educational systems state that working with gifted students is of special interest and that it will be given a special priority. However, it seems that this is only a declarative commitment, since the care for these students comes down to organizing competitions and preparing the students for several days before the competitions. We believe that this approach does not even remotely meet the needs of gifted students, therefore, in this paper we have made an attempt to develop a curriculum for working with mathematically gifted students aged 16-17, that is, for students in the second year of secondary education.
Keywords: gifted students, curriculum, curriculum goals and activities